Four new species of mealybug (Pseudococcidae) and a new species of soft scale (Coccidae: Coccoidea: Hemiptera) from Greenland and redescriptions of a mealybug and a soft scale from Arctic Canada - Gertsson, Carl-Axel; Hodgson, Chris (Zootaxa, 2005)
The adult females of four new mealybug species are described from Greenland (Atrococcus groenlandensis, Chorizococcus multiporus and Trionymus bocheri and T. elymus) and a key is provided for all mealybug species known from Greenland; a new species of Coccidae is also described from Greenland (Pulvinaria glacialis). In addition, the adult females of the mealybug Atrococcus altoarcticus Richards and the soft scale Pulvinaria ellesmerensis Richards from arctic Canada are redescribed and compared with their close relatives from Greenland.